Fertility in congenital adrenal hyperplasia due to 21-hydroxylase deficiency: a review - Roszkowska, Zuzanna; Bobrowicz, Małgorzata; Betlejewska, Joanna; Hubska, Joanna; Rak-Makowska, Beata; Ambroziak, Urszula (Frontiers in Endocrinology, 2025)
Congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency is a rare autosomal recessive disorder affecting adrenal steroidogenesis, leading to cortisol deficiency, androgen oversecretion and adrenal glands’ hyperplasia. While neonatal screening programs facilitate early diagnosis and treatment, CAH remains a complex condition with significant implications for fertility in both men and women. Women with CAH may experience menstrual irregularities, anovulation, prenatal virilization and psychological problems, while men face the problem of testicular adrenal rest tumors (TARTs), which can impair spermatogenesis, as well as experience sexual dysfunctions. Despite advances in the management of CAH, the issues of fertility and quality of sexual life still pose a challenge in this group of patients. This review aims to present the topic of fertility in CAH, taking into consideration the latest research and novel treatment options and underscores the importance of neonatal screening programs as well as personalized, team-based management to improve both reproductive outcomes and quality of life in CAH patients.